Hereditary spastic paraparesis presenting as cerebral palsy due to ADD3 variant with mechanistic insight provided by a Drosophila γ‐adducin model. Issue 6 (18th September 2022) - Sanchez Marco, Silvia Beatriz; Buhl, Edgar; Firth, Rose; Zhu, Bangfu; Gainsborough, Mary; Beleza‐Meireles, Ana; Moore, Sandra; Caswell, Richard; Stals, Karen; Ellard, Sian; Kennedy, Cameron; Hodge, James J. L.; et al.
Abstract: Cerebral palsy (CP) causes neurological disability in early childhood. Hypoxic‐ischaemic injury plays a major role in its aetiology, nevertheless, genetic and epigenetic factors may contribute to the clinical presentation. Mutations in ADD3 (encoding γ‐adducin) gene have been described in a monogenic form of spastic quadriplegic cerebral palsy (OMIM 601568). We studied a 16‐year‐old male with spastic diplegia. Several investigations including neurometabolic testing, brain and spine magnetic resonance imaging (MRI) and CGH‐Array were normal. Further, clinical genetics assessment and whole exome sequencing (WES) gave the diagnosis. We generated an animal model using Drosophila to study the effects of γ‐adducin loss and gain of function. WES revealed a biallelic variant in the ADD3 gene, NM_016824.5(ADD3): c.1100G > A, p.(Gly367Asp). Mutations in this gene have been described as an ultra‐rare autosomal recessive, which is a known form of inherited cerebral palsy. Molecular modelling suggests that this mutation leads to a loss of structural integrity of γ‐adducin and is therefore expected to result in a decreased level of functional protein. Pan‐neuronal over‐expression or knock‐down of the Drosophila ortholog of ADD3 called hts caused a reduction of life span and impaired locomotion thereby phenocopying aspects of the human disease. Our animal experiments present a starting point to understand the biological processes underpinning the clinical phenotype and pathogenic mechanisms, to gain insights into potential future methods for treating or preventing ADD3 related spastic quadriplegic cerebral palsy. Abstract : Mutations in ADD3 (encoding γ‐adducin) gene have been described in a monogenic form of spastic quadriplegic cerebral palsy (OMIM 601568).Molecular modelling suggests that this mutation leads to a loss of structural integrity of γ‐adducin and is therefore expected to result in a decreased level of functional protein. Pan‐neuronal over‐expression or knock‐down of the Drosophila ortholog of ADD3 called hts caused a reduction of life span and impaired locomotion thereby phenocopying aspects of the human disease.